2010
DOI: 10.3390/e12040772
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Model Reduction and Entropy-based Lyapunov Functions in Chemical Reaction Kinetics

Abstract: In this paper, the structural properties of chemical reaction systems obeying the mass action law are investigated and related to the physical and chemical properties of the system. An entropy-based Lyapunov function candidate serves as a tool for proving structural stability, the existence of which is guaranteed by the second law of thermodynamics. The commonly used engineering model reduction methods, the so-called quasi equilibrium and quasi steady state assumption based reductions, together with the variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The artefacts commonly occur due to the asymptotic parameters in Tikhonov's theorem not being sufficiently small. For example, it has been shown that exotic phenomena such as multistability and oscillations can exist in a degenerate system, while not existing in the corresponding total system [27,30]. Using Korzukhin's and Tikhonov's theorems, a family of kinetic total systems for an arbitrary nonkinetic polynomial degenerate system can be constructed, as is now shown.…”
Section: The Quasi-steady State Transformationmentioning
confidence: 87%
See 1 more Smart Citation
“…The artefacts commonly occur due to the asymptotic parameters in Tikhonov's theorem not being sufficiently small. For example, it has been shown that exotic phenomena such as multistability and oscillations can exist in a degenerate system, while not existing in the corresponding total system [27,30]. Using Korzukhin's and Tikhonov's theorems, a family of kinetic total systems for an arbitrary nonkinetic polynomial degenerate system can be constructed, as is now shown.…”
Section: The Quasi-steady State Transformationmentioning
confidence: 87%
“…Using the fact that a ∈ (−1, 0) and the constraints (30), it follows thatk 2 0 from (29) is negative,k 2 0 < 0. Thus, (Ψ T P)(x;k) has a cross-negative term, and the statement of the theorem follows.…”
Section: Lemma 42 Functionmentioning
confidence: 99%
“…Physically, the constructed equations correspond to chemical reactions in a system with constant volume and temperature. For other classical conditions (isobaric systems, isolated systems, etc, the Lyapunov functionals are also known (see, for example, [26,48]). …”
Section: Preliminaries: Mal Detailed Balance and H-theoremsmentioning
confidence: 99%
“…This is usually the consequence of model simplification based on assumptions [7]. However these assumptions are sometimes forgotten or not known explicitly.…”
Section: Introductionmentioning
confidence: 99%